2014
DOI: 10.1099/mic.0.082347-0
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans leukotoxin (LtxA; Leukothera) induces cofilin dephosphorylation and actin depolymerization during killing of malignant monocytes

Abstract: Leukotoxin (LtxA; Leukothera), a protein toxin secreted by the oral bacterium Aggregatibacter actinomycetemcomitans, specifically kills white blood cells (WBCs). LtxA binds to the receptor known as lymphocyte function associated antigen-1 (LFA-1), a β2 integrin expressed only on the surface of WBCs. LtxA is being studied as a virulence factor that helps A. actinomycetemcomitans evade host defences and as a potential therapeutic agent for the treatment of WBC diseases. LtxA-mediated cell death in monocytes invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…In particular, Itgal encodes CD11a, which is an integrin component of LFA-1. LFA-1 is considered a receptor for A. actinomycetemcomitans leukotoxin and is required for A. actinomycetemcomitans internalization, which initiates cell death (27). Since MK2 deficiency downregulated Itgal, the decreases in the amount of macrophage infiltrate seen were not likely due to A. actinomycetemcomitans-induced monocyte apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, Itgal encodes CD11a, which is an integrin component of LFA-1. LFA-1 is considered a receptor for A. actinomycetemcomitans leukotoxin and is required for A. actinomycetemcomitans internalization, which initiates cell death (27). Since MK2 deficiency downregulated Itgal, the decreases in the amount of macrophage infiltrate seen were not likely due to A. actinomycetemcomitans-induced monocyte apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, some RTX toxins can be engineered for therapeutic applications. The A. actinomycetemcomitans LtxA leukotoxin is being developed as a targeting agent (Leukothera®) for the treatment of hematological malignancies or autoimmune/inflammatory diseases, characterized by chronic activation of leukocytes expressing high levels of LFA-1 [387][388][389][390]. The B. pertussis CyaA toxin is used as an antigen delivery vehicle to trigger cell-mediated immune responses against a variety of antigens [379,391,392].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that caspases play an important role in LtxA-mediated death of lymphocytes [11, 14, 15, 17, 26]. Therefore, to begin to decipher the mechanism of LtxA-mediated death of malignant lymphocytes, we examined the role of caspases.…”
Section: Resultsmentioning
confidence: 99%
“…After binding to LFA-1, LtxA induces the uptake of the LFA-1/LtxA complex and delivery to the lysosome, where the lysosomal membrane is disrupted and cathepsin D is released [11]. This mechanism of cell death in monocytes is very rapid and irreversible also resulting in cofilin dephosphorylation and actin depolymerization [15]. However, we found that lymphocytes do not undergo a similar mechanism of cell death since inhibitors of the lysosomal pathway do not affect LtxA-mediated cell death in these cells [11].…”
Section: Introductionmentioning
confidence: 99%